Proceedings of the Ocean Drilling Program, 159 Scientific Results 1998
DOI: 10.2973/odp.proc.sr.159.039.1998
|View full text |Cite
|
Sign up to set email alerts
|

Upper Cretaceous, K/T boundary, and Paleocene agglutinated foraminifers from Hole 959D (Côte d'Ivoire-Ghana Transform Margin)

Abstract: Upper Cretaceous agglutinated foraminifer assemblages from Hole 959D of Ocean Drilling Program (ODP) Leg 159, Côte d'Ivoire-Ghana Transform Margin, reflect the subsidence history and paleoceanography of the widening equatorial Atlantic gateway. Five benthic foraminifer assemblage types are recognized: (1) Santonian and the lowermost Campanian assemblages (Cores 159-959D-65R and 64R) are characterized by the occurrence of bathyal calcareous benthic foraminifers with an increasing proportion of agglutinated fora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Reports on Coniacian to Lower Campanian Organic Carbon -Rich Marine Sediments Representing the OAE-3 (Coniacian-Santonian) and the Succeeding ''Biosiliceous Event'' (Lower Campanian) as Proposed byKuhnt et al [1998] in the Atlantic and Tethyan Ocean a…”
mentioning
confidence: 99%
“…Reports on Coniacian to Lower Campanian Organic Carbon -Rich Marine Sediments Representing the OAE-3 (Coniacian-Santonian) and the Succeeding ''Biosiliceous Event'' (Lower Campanian) as Proposed byKuhnt et al [1998] in the Atlantic and Tethyan Ocean a…”
mentioning
confidence: 99%
“…The authors of [34] indicated the universal biostratigraphical use of C. gigantea abundant assemblages in the Outer Carpathians, which was the basis for establishing the Caudammina gigantea acme zone of late Santonian-early Maastrichtian age. The Caudammina gigantea zone is used commonly for North Atlantic stratigraphy; it ranges from middle-upper Campanian to Maastrichtian ( [35][36][37][38] and references therein). Similar use was introduced in the Contessa Highway section near Gubbio Italy [39].…”
Section: Remarksmentioning
confidence: 99%
“…It is not so common as the Eocene acme. In different intervals of the Paleocene, an increase in S. spectabilis is commonly noted from the Atlantic-Tethyan and Boreal realms ( [1,35,89,[104][105][106] and references therein). It is one of the most common species in the Paleocene at Site 1511 in the Tasman Sea [69].…”
Section: Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…The first occurrence (FO) of Caudammina gigantea was observed in sample 15 (lower part of the CC22 Zone of calcareous nannoplankton). Caudammina gigantea was considered by Kuhnt et al (1998), Bąk (2000), and Cetean et al (2011), as not living above the middle bathyal zone and it seems that its first occurrence is diachronous along the Carpathians. In the Polish Outer Carpathians, Olszewska (1997) Planktonic foraminifera occur only in the basal part of the section (grey marlstones) with high proportions in samples 4 and 11 (Fig.…”
Section: Biostratigraphymentioning
confidence: 99%